Linking economic growth pathways and environmental sustainability by understanding development as alternate social–ecological regimes - Cumming, Graeme S. (Proc Natl Acad Sci U S A, 2018)
Scientists understand how global ecological degradation is occurring but not why it seems to be so difficult to reverse. We used national-level data and a mathematical model to provide an empirical test of the hypothesis that national economies display two distinct economic regimes that are maintained by self-reinforcing feedbacks between natural resources and society. Our results not only support previous findings that two distinct groups exist, but also show that countries move toward one of these two different equilibrium points because of their different patterns of natural resource use and responses to population growth. At the less economically developed equilibrium point maintained by “green-loop” feedbacks, human populations depend more directly on ecosystems for income. At the more economically developed equilibrium point maintained by “red-loop” feedbacks, nonecosystem services (e.g., technology, manufacturing, services) generate the majority of national gross domestic product (GDP), but increasing consumption of natural resources means that environmental impacts are higher and are often exported (via cross-scale feedbacks) to other countries. Feedbacks between income and population growth are pushing countries farther from sustainability. Our analysis shows that economic growth alone cannot lead to environmental sustainability and that current trajectories of resource use cannot be sustained without breaking feedback loops in national and international economies.